2019
DOI: 10.1021/jacs.9b01839
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Ultralow Detection Limit of Amines using a Thiadiazole-Functionalized Zr(IV)-Based Metal–Organic Framework

Abstract: A luminescent Zr­(IV)-based metal–organic framework (MOF), with the underlying fcu topology, encompassing a π-conjugated organic ligand with a thiadiazole functionality, exhibits an unprecedented low detection limit of 66 nM for amines in aqueous solution. Markedly, this ultralow detection is driven by hydrogen-bonding interactions between the linker and the hosted amines. This observation is supported by density functional theory (DFT) calculations, which clearly corroborate the suppression of the twisting mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
209
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(210 citation statements)
references
References 36 publications
1
209
0
Order By: Relevance
“…The highest fluorescence quenching ability of trinitrophenol can be attributed to both energy and electron transfer processes as well as electrostatic interactions between the hydroxyl group of trinitrophenol and the Lewis basic N-donor sites of the thidiazole-based ligand. In 2019, the same MOF has also been exploited by Eddaoudi and co-workers (KAUST, SAU) for the detection of amines in ultra-low traces (via fluorescence turn-on) in aqueous solutions [80]. This extremely powerful action is driven by hydrogen bonding interactions between the linker and the hosted amines.…”
Section: Thiadiazole-based Mofs and Cps As Luminescent Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest fluorescence quenching ability of trinitrophenol can be attributed to both energy and electron transfer processes as well as electrostatic interactions between the hydroxyl group of trinitrophenol and the Lewis basic N-donor sites of the thidiazole-based ligand. In 2019, the same MOF has also been exploited by Eddaoudi and co-workers (KAUST, SAU) for the detection of amines in ultra-low traces (via fluorescence turn-on) in aqueous solutions [80]. This extremely powerful action is driven by hydrogen bonding interactions between the linker and the hosted amines.…”
Section: Thiadiazole-based Mofs and Cps As Luminescent Sensorsmentioning
confidence: 99%
“…This observation is supported by density functional theory (DFT) calculations, which clearly corroborate the suppression of the twisting motion of the benzo[c] [1,2,5]thiadiazole core in the presence of the amine guest, reducing significantly the non-radiative recombination pathways and subsequently, enhancing the emission intensity ( Figure 7). In 2019, the same MOF has also been exploited by Eddaoudi and co-workers (KAUST, SAU) for the detection of amines in ultra-low traces (via fluorescence turn-on) in aqueous solutions [80]. This extremely powerful action is driven by hydrogen bonding interactions between the linker and the hosted amines.…”
Section: Thiadiazole-based Mofs and Cps As Luminescent Sensorsmentioning
confidence: 99%
“…However, the literature has seen little exploration regarding the engineering of the MOF structure properties to regulate the dynamic ranges and sensitivities of MOF‐based probes, though they have been widely investigated and developed for detecting various analytes. [ 18–30 ] Moreover, only a few of these MOF‐based sensors are used for recognizing disease‐related markers, [ 23,24,28 ] and they are also limited to an unoptimizable detection range with insufficient responses to small changes of the targets concentration, which is unsatisfactory for precise diagnosis of disease. Herein, we report a novel strategy to engineer a luminescent lanthanide‐based metal–organic framework (Eu‐ZnMOF) biosensor with tunable detection performances for tracing the overexpressed VMA in urine ( Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there is a pressing need for detection of amines in the assessment of food safety and diseases prevention and control [230]. Mallick et al [231] reported a "turn-off" sensor based on the luminescent Zr-BTDB-fcu-MOF with ultrasensitive detection for amines as low as 66 nM. This ultrasensitive detection is according to hydrogen bonding between the Zr-MOF and the amines, the amines could turn-on the luminescence and enhance the emission intensity.…”
Section: Aminesmentioning
confidence: 99%